Studi Perbandingan Struktur Kepemilikan, Ukuran Perusahaan, Debt To Assets Ratio, Growth Dan Manajemen Laba Pada Bank Konvensional Dan Syariah Di Indonesia - Wadhitira, Wadhitira (2016)
This study in Islamic and conventional banks in Indonesia, with the aim of knowing the ownership structure, company size, debt to assets ratio in Islamic banks with a debt to assets ratio, growth and earnings management in Islamic banks with the size of the company in a conventional bank. This research method using populasiseluruh Islamic banks and conventional banks in Indonesia, using sampelbank shariah and conventional banks in Indonesiasebanyak 10 bankyang consists of five Islamic banks and conventional banks 5 in the period 2010-2014. Mechanical sampling or the sampling method used is purposive sampling sampling.purposive is a technique of determining the number of samples with a certain considerations. The analytical tool used: 1) Descriptive Statistics and 2) test the independent t test